Influência do exercício prévio pesado na performance aeróbia de curta duração realizada com diferentes estratégias de distribuição da intensidade em indivíduos treinados e não treinados no ciclismo - Caritá, Renato Aparecido Corrêa [UNESP] (2014)
The aim of this study was to analyze the influence of prior heavy exercise on short-term aerobic performance with different strategies of distribution of the intensity in trained (T) and untrained (UNT) individuals in cycling. In the first laboratory visit, subjects underwent a protocol for the determination of lactate threshold (LT), maximum oxygen consumption ( O2max) and maximal power (Pmax). In the following four occasions the volunteers performed tests with constant load (75%, 80%, 90% and 100%Pmax) until volitional exhaustion in random order to determine the critical power (CP) and anaerobic work capacity (AWC). From the 6th to the 11th visit, in random order, the following experimental sessions were performed: 1) Even start (ES): 120 s of constant workload exercise in P3min followed by a sprint (all out) 60 s; 2) Slow start (SS): 90 s of exercise with initial load of 10% below P3min, increasing linearly until it reaches 110% of P3min, 30 s of constant workload at P3min, followed by an all out sprint of 60 s; 3) Fast start (FS): 90 s of exercise with initial load of 10% above P3min, decreasing linearly to reach 90% of P3min, 30 s of constant workload at P3min, followed by an all out sprint of 60 s. All these conditions were performed with and without a prior heavy exercise. There was significant reduction on mean response time (MRT) at SS (26.2  6.1 s), ES (23.9  7.5 s) and FS (22.4  7.8 s) after prior exercise when compared to the control condition (SS = 33.7  7.3 s; ES = 30.3  8.6 s; FS = 29.2  11 s) (p < 0.05) in the UNT group. There was interaction of the factors strategy and prior exercise only in the T group (p < 0.05). There was effect of pacing when comparing the FS (32.0  5.6 s) and ES (32.1  4.7 s) with FS (26.6  4.0 s) (p < 0.05) during the control condition. There was significant reduction of MRT for the SS (25.9  4.8 s) and ES (24.6  4.7 s) conditions after prior exercise (p < 0.05). With...